Lost in the crowd: Imagining walking in synchrony with a crowd increases affiliation and deindividuation - Crossey, Benjamin Philip (PLoS One, 2021)
Moving in time with others—interpersonal coordination—increases affiliation, helping behaviours and gives rise to a host of other prosocial outcomes. Recent research suggests that merely imagining coordination may lead to similar social effects. In the present study, participants were asked to imagine walking with a crowd in a coordinated (versus uncoordinated) way to explore the effects of imagined coordination on individuals’ perceptions of themselves and the crowd. Imagined coordination led to greater levels of deindividuation and affiliation. That is, participants were less likely to report seeing themselves as unique individuals, instead viewing themselves as a part of a group (deindividuation) and more likely to report a sense of emotional closeness (affiliation) with the imagined group. Deindividuation partially mediated the effect of imagined coordination on affiliation. This work establishes that imagined synchrony can be employed online to foster prosocial attitudes towards groups of people, and that a process of deindividuation might mediate this effect.